Equity in the Geographical Accessibility to Hospitals. The Case of de Basque Country - Cano-Fernández, Francisco Javier; Esteban-Galarza, Marisol (Revista de Estudios Andaluces, 2021)
The aim of this article is to analyse the spatial equity and efficiency of the geographical distribution of the hospital resources of Basque Country manage by the Basque Health Service (Osakidetza), under the prism of the new model of Integrated Healthcare Organisation. Using Google Earth for spatial location and extraction of geographical coordinates, a statistical analysis of population accessibility is carried out, considering time and distance to the reference Specialised Care resource. In view of the results, it has been possible to demonstrate the existence, in general, of a high level of balance between the spatial equity and efficiency mentioned, since 90% of the population has a temporal and spatial accessibility that can be qualified as between optimum and normal, with an access time of 0 to 20 minutes or a distance of between 0 and 20 km. Therefore, taking into account the above, the improvement actions should be directed towards the 10% of the most disadvantaged population, with initiatives such as the redefinition of the health map; the establishment of collaboration agreements with other regions; the improvement of communication infrastructures, without excluding other actions that could achieve the same objective.